1949
DOI: 10.1136/bmj.1.4591.6
|View full text |Cite
|
Sign up to set email alerts
|

Antihistamine Drugs in Acute Nephritis

Abstract: CLINICAL AND SOCIAL PROBLEMS OF EPILEPSY ERDITLSJOURNALattacks; prominent among these are headache and a desire to sleep, signs of injury, tongue-biting, incontinence of urine, vomiting, and soreness of muscles.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
3
0

Year Published

1951
1951
1961
1961

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Initial experience with this drug suggested that it might be of value (Craig, Clark and Chalmers, 1949) and the last 62 consecutive cases of the series reported here were treated with this drug for varying periods. No evidence was obtained that mepyramine maleate influenced the mortality or the duration or severity of the initial illness, nor did it diminish the incidence of cases left with signs of permanent renal damage.…”
mentioning
confidence: 96%
“…Initial experience with this drug suggested that it might be of value (Craig, Clark and Chalmers, 1949) and the last 62 consecutive cases of the series reported here were treated with this drug for varying periods. No evidence was obtained that mepyramine maleate influenced the mortality or the duration or severity of the initial illness, nor did it diminish the incidence of cases left with signs of permanent renal damage.…”
mentioning
confidence: 96%
“…Even if this were to occur the effect upon long-term prognosis Would not be clearly proved until a large series had been followed up, although the probability of such effect would be strong enough to justify the optimistic use of the treatment. Craig, Clark, and Chalmers (1949) reported their experience in the use of mepyramine maleate (" anthisan ") in the treatment of a series of cases. The average duration of the disease in their treated series was two to three weeks, and in the series of untreated cases, with which it was compared, about four months.…”
mentioning
confidence: 99%
“…The experiences reported in the English literature on the clinical and experimental use of anti-histamines in nephritis have been limited and conflicting. Mepyramine maleate (Anthisan) used in two groups of patients produced slight benefit in one group (4) and no change in the other group (5). Experimentally, tripelennaminc hydrochloride (Pyribenzamine) has been shown to delay the onset of albuminuria, but not to alter the histologic findings in nephro-toxic nephritis (6).…”
mentioning
confidence: 99%